Dosage-related nature of escitalopram treatment-emergent mania/hypomania: a case series - Yamaguchi Y (Dove Medical Press, 2018)
Yasunari Yamaguchi, Sohei Kimoto, Takeshi Nagahama, Toshifumi Kishimoto Department of Psychiatry, Nara Medical University School of Medicine, Kashihara, Japan Objective: Several studies have documented that treatment with various antidepressant agents can result in mood switching during major depressive episodes. Escitalopram, one of the newer selective serotonin reuptake inhibitors (SSRIs), is considered preferable due to its relatively high efficacy and acceptability. Although a few cases of escitalopram treatment-emergent mania have been reported, it remains unknown whether this effect is dose-related.Method: In the present report, we discuss three cases of treatment-emergent mania/hypomania in patients receiving escitalopram for major depressive episodes. No patients had a family or personal history of bipolar disorder.Results: In all three cases, manic or hypomanic symptoms emerged within 1 month right after the dosage of escitalopram was increased to 20 mg/day. Moreover, manic episodes subsided as the dosage of escitalopram was reduced. Mood switching was not observed after the cessation of escitalopram treatment.Conclusion: Our case series indicates that escitalopram may induce treatment-emergent mania/hypomania in a dose-related manner. Treatment at lower doses and with careful upward titration might be favorable in certain patients with bipolar depression and major depressive disorder in order to minimize the risk of mood switching. Keywords: selective serotonin reuptake inhibitor, SSRI, escitalopram, antidepressant treatment-emergent mania/hypomania, dosage-related, bipolar depression